Questions kids ask about weather - Comely, Richard; Dickie, Alison (Grolier Toronto, 1989)
Answers questions such as Does a rain dance bring rain?; Do all snowflakes look alike?; What is a chinook?; Why does the wind blow?; Why are hurricanes given names? What are the doldrums?